A nontrivial solution for a nonautonomous Choquard equation with general nonlinearity - Ding Ling; Liu Jiu; Yuan Yan-Xiang (2022)
With the help of the monotonicity trick, a nonautonomous Choquard equations with general nonlinearity is studied and a nontrivial solution is obtained.
Keywords: Természettudományok; Matematika